Influence of hydrothermal pretreatment on acidity and activity of H-GaAlMFI zeolite for the propane aromatization reaction - Choudhary, Tushar V.; Kinage, A.; Banerjee, S.; Choudhary, Vasant R. (Microporous and Mesoporous Materials, 2005)
The acidity and propane aromatization activity of H-GaAlMFI has been investigated subsequent to different hydrothermal (HT) pretreatments. Extensive degalliation of framework Ga occurred during the HT pretreatments; the framework Si/Ga ratio nearly doubled when the steam concentration was increased from 0% to 80%. The extent of degalliation and corresponding loss of strong zeolitic acidity (measured in terms of pyridine chemisorbed at 400 degrees C) was particularly severe at high (> 500 degrees C) temperatures and steam concentrations (> 40 mol%). Framework Al in the GaAlMFI zeolite was found to be very stable; the FW Si/Al ratio did not change to any appreciable extent even after severe HT pretreatments. Each of the HT pretreatment parameters (concentration of steam: 0-80%, HT temperature: 400-600 degrees C and length of HT pretreatment: 0-6 h) showed a profound influence on the propane aromatization activity. The product selectivity was, however, only mildly affected by the HT pretreatments. The following factors were found to be important for high propane aromatization activity (a) strong zeolitic acidity and (b) optimal content/dispersion of the extra-framework Ga species which are formed in situ during the HT pretreatments. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Acidity; aromatic distribution; Ga-based zeolites; hydrothermal treatment and steam; propane aromatization